2012
DOI: 10.5812/iranjradiol.5276
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Pelvic MRI for Assessment of the Depth of Myometrial Invasion and Cervical Involvement in Endometrial Cancer: Comparison of New Versus Old FIGO Staging

Abstract: BackgroundEndometrial carcinoma is a highly prevalent gynecologic malignancy. The International Federation of Gynecology and Obstetrics (FIGO) staging system underwent significant revision on 2009. Key changes in the FIGO staging system include simplification of stage I endometrial cancer and removal of cervical mucosal invasion as a separate stage. MRI is a noninvasive diagnostic method for preoperative staging of endometrial cancer.ObjectivesThe main purpose of this study was to investigate the diagnostic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…analyzed 53 patients and stated that MRI is limited in its ability to detect deep myometrial invasion with respect to the results (sensitivity, specificity, and overall diagnostic accuracy were 50.0%, 89.7% and 79.2%, respectively). Conversely, Zamani et al . reported higher sensitivity (82.4%), specificity (94.6%) and diagnostic accuracy (90.7%) in the sample of 54 patients.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…analyzed 53 patients and stated that MRI is limited in its ability to detect deep myometrial invasion with respect to the results (sensitivity, specificity, and overall diagnostic accuracy were 50.0%, 89.7% and 79.2%, respectively). Conversely, Zamani et al . reported higher sensitivity (82.4%), specificity (94.6%) and diagnostic accuracy (90.7%) in the sample of 54 patients.…”
Section: Discussionmentioning
confidence: 87%
“…Significantly more of the published work sources focus on evaluating the stage of the disease . Published studies comparing transvaginal ultrasound (TVS), MRI, and possibly PET‐CT in the diagnosis of myometrial invasion and cervical stromal involvement do not lead to entirely consensual conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Zamani F et al found a diagnostic accuracy of pelvic MRI for detection of deep myometrial invasion and cervical stromal involvement of 90.74%. 8 The authors used T2 weighted and DCE MRI sequences. Their results for diagnostic accuracy in detection of deep myometrial invasion are higher than those quoted by other authors.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 While endometrial cancer affects women in perimenopause, cervical cancer affects young women of lower socioeconomic status. 1,3 The histologic types most commonly found are adenocarcinomas followed by sarcomas in endometrial cancer, and squamous cell (80%) and mucinous carcinomas in cervical cancers.…”
Section: Introductionmentioning
confidence: 99%